SOCIAL MEDIA MARKETING ACTIVITIES DENGAN PENDEKATAN TRIANGULAR GUNA MENINGKATKAN BRAND EQUITY - Rumondang Dian Mariani; Yolanda Masnita (EBID: Ekonomi Bisnis Digital, 2024)
By analyzing and identifying the variables tested, this study examines the variables that affect brand equity mediated by perceived quality. This research uses quantitative methods with questionnaire data collection tools. Furthermore, the data that has been collected is processed using the SEM-PLS method. The results showed that the social media marketing factor can be significantly influenced by the component: perceived quality of services perceived by consumers. However, brand trust and brand love do not have a significant influence on brand equity.